Toxicity Test of HA-TCP Variation from Synthesis of Blood Shell with Fluoride Addition as Dental Remineralization Material - Ayulistya Paramita Sutarto; Ari Rosita Irmawati; Wijaya, Yongki Hadinata (Denta Journal Kedokteran Gigi, 2025)
Background: Caries is the most found problem in teeth. Caries begins with fermentation process of carbohydrates. The preventive and curative actions of white spot lesions aim to initiate and improve the process of tooth remineralization. HA TCP from the synthesis of blood shells with fluoride added is expected to be a dental remineralization agent. Objective: To determine the cytotoxicity of HA-TCP variation from the synthesis of blood clam shells (Anadara granosa) with fluoride added as a dental remineralization material. Materials and Methods: This type of research is true experimental with a post test only control design. The data from the research results were then carried out  a descriptive test and viability test followed by the Kruskal wallis test and significance test using the Chi Square Test. The number of samples was 15 which were divided into 4 groups, namely the KS (control group of cells, without the addition  of scaffolds, P1 (HA-TCP 15% with fluoride addition), P2 (HA TCP 20% with fluoride addition) and P3 (HA-TCP 25% with fluoride addition). The cytotoxicity test was carried out using MTT Assay on BHK-21 cells. Results: The results of cell viability percentages in the KS, P1, P2, and P3 groups were 100%, 61.16%, 79.12% and 88.83% respectively. Conclusion: The cytotoxicity test results  of HA-TCP variation from the synthesis of blood clam shells (Anadara granosa) with fluoride added as a dental remineralization material showed non-toxic results.